Applications of the Marcus cross relation to inner sphere reduction of O2: implications in small-molecule activation. Issue 9 (13th August 2019) - Lacy, David C.
Abstract : The Marcus cross relation is demonstrated to be applicable to inner sphere electron transfer from iron to molecular oxygen by incorporation of the Fe(iii )–O2 to Fe(iii ) + superoxide BDFE in K eq . A few case-studies are provided as working examples. Abstract : Application of the Marcus cross relation (MCR) to determine electron transfer rate constants is well documented. In addition to outer sphere reduction/oxidation of O2 /O2 ˙ −, the MCR is also applicable for proton transfer (PT), proton-coupled electron transfer (PCET), and hydride transfer rate constants. A question this report aims to address is whether or not the MCR can predict rate constants for inner sphere electron transfer (ISET) reactions between iron complexes and O2 . By including the iron–superoxide bond dissociation energy (BDFEFe–O2 ) into the MCR equilibrium constant, close values to experimental inner sphere O2 reductions are estimated. This insight of including the iron–superoxide binding energy as a design element for the development of synthetic oxygenases is considered.